Social interactions and collecting practices mediated by the cyberspace: A nethnography with fountain pens collectors (Research, Society and Development, 2022)
This research aimed to analyze the meanings that permeate collector’s practices when collecting fountain pens. Based on a nethnography conducted in a social network group of collectors, interactions and interviews were carried for data collection. Main findings showed that, for the collector, the object’s meanings are built on the continuous socialization of information and images about fountain pens mediated by cyberspace. These practices reinforce the meanings of being a collector and underline shared beliefs and narrow consumption patterns. Displaying the possessed objects means the acceptance ritual in a specific group and this belonging results in social recognition and reputation to the possessor. The studied virtual community is a space for resignification of collecting practices, reinforcing the sense of fellowship among members. Fear of decreasing the collection, financial problems, nostalgia, heritage, search for immortality, hobbies, possessiveness, passion, passing rituals, relatives’ criticism, and constant escapes from reality were identified in these collecting practices. This research has, as main contribution to theory, is that we identified how collectors built the meaning of collecting fountain pens and socializing their pieces/histories thanks to the mediated way of meaning construction. Through the internet and specialized communities, collectors found a way of building and strengthening the meaning and their beliefs in a way that they would not do in real life.